2020
DOI: 10.1017/s0007114520001415
|View full text |Cite
|
Sign up to set email alerts
|

Effect of walnut consumption on markers of blood glucose control: a systematic review and meta-analysis

Abstract: Type 2 diabetes mellitus is a chronic disease increasing in global prevalence. Although habitual consumption of walnuts is associated with reduced risk of CVD, there is inconsistent evidence for the impact of walnut consumption on markers of glycaemic control. This systematic review and meta-analysis aimed to examine the effect of walnut consumption on markers of blood glucose control. A systematic search of Medline, PubMed, CINAHL and Cochrane databases (to 2 March 2019) was conducted. Inclusion criteria were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 68 publications
2
18
0
Order By: Relevance
“…The four studies included for the HOMA-IR outcome also had moderate statistical heterogeneity, but overall did not show an effect of walnut consumption. These findings concur with a recently published systematic review and meta-analysis, which found no significant effects of walnut consumption on HbA1c and HOMA-IR [73]. Likewise, our meta-analyses for the inflammation markers hsCRP, IL-6, TNFA, E-Selectin, sICAM-1 and sVCAM-1 did not reach statistical significance.…”
Section: Discussionsupporting
confidence: 92%
“…The four studies included for the HOMA-IR outcome also had moderate statistical heterogeneity, but overall did not show an effect of walnut consumption. These findings concur with a recently published systematic review and meta-analysis, which found no significant effects of walnut consumption on HbA1c and HOMA-IR [73]. Likewise, our meta-analyses for the inflammation markers hsCRP, IL-6, TNFA, E-Selectin, sICAM-1 and sVCAM-1 did not reach statistical significance.…”
Section: Discussionsupporting
confidence: 92%
“…Current evidence supports the recommendation of tree nut (i.e., almond, pistachio, walnut) and peanut intake for the prevention and nonpharmacological therapy of chronic conditions such as, dyslipidemia, type II diabetes mellitus, hypertension and cardiovascular mortality [ 1 , 2 , 3 ]. As nuts provide a substantial amount of energy (calories/g) [ 4 ] and have a high nutritional density [ 5 ], whether nutrient consumption leads to weight gain and increased body fat is a common concern [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 87%
“…Pecans are particularly high in proanthocyanidins and ellagitannins, pistachios and almonds are high in proanthocyanidins, and walnuts are high in ellagitannins [ 101 ]. Consumption of pistachio nuts, according to 6 intervention studies, improved HOMA-IR through changes in fasting glucose [ 102 ], but a systematic review on walnuts concluded that there was no effect on fasting blood glucose or other measures of IR [ 103 ]. Although there are fewer reported studies on humans, pecan and almond consumption seem to improve HOMA-IR [ 104 , 105 ] and almonds are also effective at reducing IR in t2D patients [ 106 ].…”
Section: Dietary (Poly)phenolsmentioning
confidence: 99%